2010
DOI: 10.2466/pms.110.2.442-452
|View full text |Cite
|
Sign up to set email alerts
|

Constant-Random Practice and the Adaptive Process in Motor Learning with Varying Amounts of Constant Practice

Abstract: The adaptive process in motor learning was examined in terms of effects of varying amounts of constant practice performed before random practice. Participants pressed five response keys sequentially, the last one coincident with the lighting of a final visual stimulus provided by a complex coincident timing apparatus. Different visual stimulus speeds were used during the random practice. 33 children (M age=11.6 yr.) were randomly assigned to one of three experimental groups: constant-random, constant-random 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 5 publications
0
21
0
3
Order By: Relevance
“…structure/pattern formation (Corrêa et al, 2006(Corrêa et al, , 2007(Corrêa et al, , 2010a(Corrêa et al, , 2010b, one could think that this may not have been enough to prepare the skill structure for the diversification process. In this regards, recent studies by Ugrinowitsch et al (2010Ugrinowitsch et al ( , 2011 have shown that the extensive practice during the stabilization phase can provide the learners with more capacity to adapt.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…structure/pattern formation (Corrêa et al, 2006(Corrêa et al, , 2007(Corrêa et al, , 2010a(Corrêa et al, , 2010b, one could think that this may not have been enough to prepare the skill structure for the diversification process. In this regards, recent studies by Ugrinowitsch et al (2010Ugrinowitsch et al ( , 2011 have shown that the extensive practice during the stabilization phase can provide the learners with more capacity to adapt.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, with regard to the amount of practice we expected that there would be a critical threshold in which the acquired flexibility would be enough to promote adaptation as in the case of systems placed in a region of self-organized criticality (Kauffman, 1993;Langton, 1992;Packard, 1988). For instance, Corrêa et al (2006Corrêa et al ( , 2007Corrêa et al ( , 2010b showed that varying amounts of constant practice prior to random practice had similar effects on the adaptive process, and they concluded that the minimum amount of practice needed to the formation of a structure was enough for initiating the diversification process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations